Delayed coral recovery in a warming ocean. (9th May 2017) - Osborne, Kate; Thompson, Angus A.; Cheal, Alistair J.; Emslie, Michael J.; Johns, Kerryn A.; Jonker, Michelle J.; Logan, Murray; Miller, Ian R.; Sweatman, Hugh P. A.
Abstract: Climate change threatens coral reefs across the world. Intense bleaching has caused dramatic coral mortality in many tropical regions in recent decades, but less obvious chronic effects of temperature and other stressors can be equally threatening to the long‐term persistence of diverse coral‐dominated reef systems. Coral reefs persist if coral recovery rates equal or exceed average rates of mortality. While mortality from acute destructive events is often obvious and easy to measure, estimating recovery rates and investigating the factors that influence them requires long‐term commitment. Coastal development is increasing in many regions, and sea surface temperatures are also rising. The resulting chronic stresses have predictable, adverse effects on coral recovery, but the lack of consistent long‐term data sets has prevented measurement of how much coral recovery rates are actually changing. Using long‐term monitoring data from 47 reefs spread over 10 degrees of latitude on Australia's Great Barrier Reef (GBR), we used a modified Gompertz equation to estimate coral recovery rates following disturbance. We compared coral recovery rates in two periods: 7 years before and 7 years after an acute and widespread heat stress event on the GBR in 2002. From 2003 to 2009, there were few acute disturbances in the region, allowing us to attribute the observed shortfall in coral recovery rates to residual effects of acute heat stress plus other chronic stressors. Compared with the period before 2002, the recovery of fast‐growing Acroporidae and of "Other" slower growing hard corals slowed after 2002, doubling the time taken for modest levels of recovery. If this persists, recovery times will be increasing at a time when acute disturbances are predicted to become more frequent and intense. Our study supports the need for management actions to protect reefs from locally generated stresses, as well as urgent global action to mitigate climate change. Abstract : Our study used long‐term monitoring data from the Great Barrier Reef to estimate the reduction in coral recovery rates due to chronic stressors. Residual effects from the acute heat stress event of 2002 plus the longer term effects of chronic stressors and associated coral disease outbreaks inhibited coral recovery from 2003–2009 compared to rates we observed over 7 years leading up to the event.